Computational Studies Applied to Anti-inflammatory Drug Discovery: A Review - Scotti, Luciana; Ishiki, Hamilton M.; Ribeiro, Frederico F.; Santos, Rodrigo; de Oliveira, Rejane B.; Oliveira, Tiago Branquinho; Alves, Mateus Feitosa; Filho, Jose M. B.; Scotti, Marcus Tullius (Current Organic Chemistry, 2018)
The inflammatory process is both natural and endogenous, occurring as a response of the organism to infectious or irritant agents. Although it is an organic response to an aggressor, and should be considered beneficial, it is not. Inflammation causes pain, edema, increased temperature, and often results in decreased mobility and quality of life for the patient. Chronic disturbances such as bowel, autoimmune diseases and asthma are all examples where an inflammatory response develops. Methods involving theoretical chemistry are widely diffused both in academia and industry because of their ability to considerably reduce both time and costs in new drug discovery endeavors. They can provide useful information concerning the steric and lipophilic nature of probable drug to biological target interactions as well as establishing quantitative relationships between chemical structures and biological activity for a series of investigated compounds. Such methods assist our understanding of mechanisms of action responsible for the known biological effect, describing and explaining experimental results; where one can essentially test for outcomes before realizing bench experiments. Based on the above, this review reported in silico studies between 2007-2017 and aims to investigate how methods involving theoretical chemistry contribute to the development of new drugs which present more efficient antiinflammatory activities with fewer side effects.
Keywords: bowel diseases